y'''=z'\\ z'=z^2=>\dfrac{dz}{z^2}=dx=>-\dfrac{1}{z}=x+C_1=>y''=-\dfrac{1}{x+C_1}\\ y'=-\int\dfrac{1}{x+C_1}dx=>y'=C_2-ln(x+C_1)=>y=\int(C_2-ln(x+C_1))dx=>y=C_2x-(x+C_1)(ln(x+C_1)-1)+C_3" alt="y'''=y''^2\\ y''=z=>y'''=z'\\ z'=z^2=>\dfrac{dz}{z^2}=dx=>-\dfrac{1}{z}=x+C_1=>y''=-\dfrac{1}{x+C_1}\\ y'=-\int\dfrac{1}{x+C_1}dx=>y'=C_2-ln(x+C_1)=>y=\int(C_2-ln(x+C_1))dx=>y=C_2x-(x+C_1)(ln(x+C_1)-1)+C_3" align="absmiddle" class="latex-formula">
Проверим особые решения:
y''=0=y'''=>y'=C_1=>y=C_1x+C_2" alt="z=0=>y''=0=y'''=>y'=C_1=>y=C_1x+C_2" align="absmiddle" class="latex-formula"> - особое решение